2020
DOI: 10.1039/d0cs00560f
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule recognition of disease-relevant RNA structures

Abstract: Targeting RNAs with small molecules, a new frontier in drug discovery and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 198 publications
(305 reference statements)
3
123
0
Order By: Relevance
“…An increasing body of evidence suggests that the function of many lncRNAs is largely mediated by their interaction with RBPs or protein complexes. Thus, a promising therapeutic option for targeting lncRNAs is the use of steric hindering antisense oligonucleotides or small molecules that affect these interactions by either (1) blocking the RNA-binding domain of the protein, or (2) directly binding to and disrupting secondary and tertiary structures in the lncRNA molecule ( Meyer et al, 2020 ) ( Figure 4C ).…”
Section: Targeting Lncrnas In Neurological Disorders: Trash or Treasure?mentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing body of evidence suggests that the function of many lncRNAs is largely mediated by their interaction with RBPs or protein complexes. Thus, a promising therapeutic option for targeting lncRNAs is the use of steric hindering antisense oligonucleotides or small molecules that affect these interactions by either (1) blocking the RNA-binding domain of the protein, or (2) directly binding to and disrupting secondary and tertiary structures in the lncRNA molecule ( Meyer et al, 2020 ) ( Figure 4C ).…”
Section: Targeting Lncrnas In Neurological Disorders: Trash or Treasure?mentioning
confidence: 99%
“…Although still early, it has been shown that small molecules can target several classes of RNA besides lncRNAs, including miRNAs , repeat expansion regions, mRNAs encoding for intrinsically disordered proteins, splicing modifiers and motifs located at the 5′- and 3′- untranslated regions (5′- and 3′- UTRs, respectively) ( Meyer et al, 2020 ; Yu et al, 2020 ). Recently, Risdiplam received FDA approval for the treatment of SMA ( U.S. Food & Drug Administration, 2020 ), and Branaplam is undergoing clinical trials as a therapy for the same disease as well as a for HD ( ClinicalTrials.…”
Section: Targeting Lncrnas In Neurological Disorders: Trash or Treasure?mentioning
confidence: 99%
See 1 more Smart Citation
“…The action mechanism of cisplatin involves DNA binding, halting of replication, and induction of apoptosis [ 1 ]. In order to treat human diseases such as microorganism infections and genetic disorders, which rank among the most difficult diseases to tackle, the paradigm has recently shifted to RNA targeting with small molecules [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, highly speci c RNA/ligand pairs can nd broad use in diverse applications. As interest in RNA as a target for small molecule drugs has increased, so has the need for information about the design of RNA-targeting probes [22][23][24] . Understanding the chemical features that impact RNA crosslinking e ciency would in uence probe design, as well inform interpretation of results from experiments that use these probes.…”
Section: Introductionmentioning
confidence: 99%